Amelioration of soil acidity by liming for rice grown on acid sulphate soil in Peninsular Malaysia - Azman, Elisa Azura (2012)
A study was conducted in Merbok, Kedah, Malaysia. The study area was a paddy field on acid sulfate soil classified as Merbok Series (Typic Sulfaquents). This soil is highly acidic containing high Al concentration. Around 3000 ha of land in Merbok,Kedah are cultivated with rice, variety MR 219. Currently, paddy yield is less than 2 t ha-1 season-1, this is below the national average of 4 t ha-1 season-1 . Therefore, the objective of this study was to suggest ways of ameliorating an acid sulfate soil in Merbok, Kedah, Malaysia. A series of laboratory experiments, glasshouse studies and field trials were conducted. The first study is laboratory experiment. The objective was to determine the effects of high Al concentration and low pH on rice seeds germination, root morphology and organic acids release. Rice seeds (MR 219) were separately exposed into two conditons which are in solutions containing various concentration of Al (10, 20, 30,40 and 50 μM) and various water pH (3, 4, 5, 6 and 7) which the pH was adjusted using 0.01 M HCl or NaOH. Results of the study showed that root length decreased with increasing Al concentrations, while the opposite was true for the pH. The trend for the change of root surface area with Al concentration and pH is the same as that of the root length. The critical Al concentration for rice growth is 15 μM and the optimal pH for rice root to grow is 6. At low pH and high Al concentration, the rice roots secreted citrate and/or oxalate which subsequently formed Al-citrate and Aloxalate,respectively. This, to a certain extent, had reduced Al toxicity. This is the mechanism of rice slight tolerance to Al toxicity. The second study is glasshouse study. The objective was to determine the effects of lime application on the soil chemical properties and the growth of rice under glasshouse conditions. GML and hydrated lime were applied 2 weeks, while liquid lime was applied a day prior to rice seeding; MR 219 rice variety was used in this experiment. It was found that the application of 4 t ha-1 of GML had produced the highest rice yield of 8.2 t ha-1. Relative rice yield is negatively correlated with the soil pH. At harvest, the soil pH exceeded 6 for all the treated soils and this showed that as soil pH increased, exchangeable Ca increased. Soil treated with 2 t ha-1 of hydrated lime gave the highest exchangeable Ca in the soil of 11.86 cmolc kg-1 soil. At this rate of application, the concentration of Ca in the root was 0.12%. The third study was field trial conducted in Merbok. The objective was to increase rice production on an acid sulfate soil under rain-fed condition in Merbok, Kedah, Malaysia, using various lime sources. The soil was treated with ground magnesium limestone, hydrated lime and liquid lime at the specified rate. Rice variety MR 219 was tested which is the most common variety grown in Malaysia right now. The result showed that soil pH was < 3.5 and exchangeable Al was very high throughout the soil depth. Water pH in the rice field before treatment was 3.7, while Al concentration was 878 μM. The first crop of rice was subjected to drought during the vegetative growth, while the subsequent crop was infested with rice blast. In spite of that, the results showed that application of 4 t GML ha-1 gave a reasonably good yield of 3.5 t ha-1, the best among the treatments. The ameliorative effects of lime application had been continued into the second season. From this study, the suitable liming material to be used to alleviate acid sulfate soils at Merbok is 4 t ha-1 of GML costing about RM 1260.